The Franco-Algerian War: Narrating the Failure of the French Imperialist Project in Norman Lewis’s Darkness Visible (1960) - Aissat, Karima (Jordan Journal of Modern Languages & Literatures, 2024)
This article examines the political attitude towards representing French colonialism to Algeria during the Franco-Algerian war (1954-1962) in Darkness Visible (1960) by the Welsh-British Norman Lewis. It probes how Lewis’s novel portrays French colonial project, which was intended to bring civilization to Algerians, as a failure through raising an anti- colonial thought. In the novel, the Mission does not only fail to achieve the goals of its agenda, but also fails in the sense that it exposes more negative consequences of exploitation, oppression, and cultural destruction of the colonized people. The paper also scrutinizes Lewis’s use of immediacy of the narrative and Manicheanism in characterization as literary device to critique French colonial practices against the natives; while, in parallel, Lewis highlights the aspect of nationalist mobilization to unearth the legitimacy of the Algerians fighting for liberty. Therefore, this article ventures thematically into Darkness Visible within anti- colonial discourse parameters.